EFFECTS OF JIGSAW, NUMBERED-HEADS-TOGETHER AND GROUP INVESTIGATION COOPERATIVE LEARNING STRATEGIES ON SECONDARY SCHOOL STUDENTS' LEARNING OUTCOMES IN ENGLISH GRAMMAR, OGUN STATE, NIGERIA (2012)
Low language proficiency, arising from poor instructional strategies and defective knowledge of English grammar, contributes to persistent decline in students’ performance across school subjects. Past studies on cooperative learning strategies focused on oral language teaching and vocabulary development. However, little attention has been devoted to the use of these strategies in teaching and learning grammar. Consequently, this study investigated the effects of cooperative learning strategies (Jigsaw, Numbered-Heads-Together and Group Investigation) on secondary school students’ learning outcomes in English grammar. It also explored the interaction effects of gender and parental educational support on the dependent variables. The study employed pretest-posttest, control group, quasi-experimental design, using factorial matrix of 4X2X2. Intact classes comprising 350 students from eight secondary schools in Ijebu-Ode local government area of Ogun state were selected and randomly assigned to three treatment and one control groups. Three instruments were used: Achievement Test in English Grammar (r = 0.87); Attitude to English Grammar Questionnaire (r = 0.83); Parental Educational Support Questionnaire (r = 0.83). Instructional guides for each of the experimental and control groups; and an assessment guide for research assistants were applied. Seven hypotheses were tested at 0.05 level of significance. Data were subjected to Analysis of Covariance, Multiple Classification Analysis and Scheffe posthoc. There was significant main effect of treatment on students’ achievement in English grammar (F(3,333) = 161.67; p < 0.05). Participants in the Group Investigation Cooperative strategy group had the highest achievement score ( x = 37.02) followed by Jigsaw group ( x =33.97); Numbered-Heads-Together group ( x = 30.48) cooperative strategies; and Modified lecture method ( x = 25.77). Also, there was significant main effect of treatment on students’ attitude to English grammar (F(3,333) = 7.87; p < 0.05). Participants in the Group Investigation cooperative strategy group had the highest attitude score ( x = 13.67) followed by those in the Numbered-Heads-Together group ( x = 12.21); Jigsaw ( x = 12.19) cooperative strategies; and Modified lecture method ( x = 11.56). Female students had higher achievement score ( x = 32.35) than their male counterparts ( x = 31.46). Gender and Parental Educational Support had no significant effect on students’ attitude to English grammar. Students with high parental educational support had higher achievement score ( x = 33.60) than students with low parental educational support ( x = 28.88). There was significant interaction effect of gender and treatment on students’ achievement (F(3,333) = 3.88; p < 0.05) but no significant effect of gender and treatment on students’ attitude. There was significant interaction effect of parental educational support and treatment on students’ achievement (F(3,333) = 4.99; p < 0.05) but no significant effect of parental educational support and treatment on students’ attitude.Cooperative learning instructional strategies have positive effect on students’ learning outcomes in English grammar. Students’ poor achievement and unfavourable attitude to grammar could be improved using cooperative learning strategy. It is, therefore, recommended that teachers should be encouraged to use the Group Investigation cooperative learning strategy to improve students’ performance in English grammar.